2015
DOI: 10.1123/jsm.2013-0211
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Succession and Performance: An Application to College Football

Abstract: This article examines the impact of leader succession on organizational performance. We argue that both time and size of program are critical factors that need to be considered to appropriately determine the impacts of the leader succession on performance. We focus our analysis on the National Collegiate Athletic Association (NCAA) Football Bowl Subdivision (FBS) and examine the effect of performance-related coaching firings on on-field performance (win-loss percentage, Sagarin rating, Sagarin rank) and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In a similar study, Canella and Rowe 23 examined the effect of ability and experience on the results of succession in Major League Baseball. Similar to Pfeffer and Blake, 21 Canella and Rowe found that managerial succession did not have any effect on team performance, supporting ritual scapegoating theory. 23 However, the authors found that teams with managers of higher ability (i.e.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In a similar study, Canella and Rowe 23 examined the effect of ability and experience on the results of succession in Major League Baseball. Similar to Pfeffer and Blake, 21 Canella and Rowe found that managerial succession did not have any effect on team performance, supporting ritual scapegoating theory. 23 However, the authors found that teams with managers of higher ability (i.e.…”
Section: Introductionsupporting
confidence: 69%
“…Despite much of the existing literature indicating that coaches are scapegoats for losing and that coaching changes do not translate to more wins, 7,[20][21][22] intercollegiate athletic coaches are routinely replaced for low performance. Pressure from students, fans, alumni, and a variety of other stakeholders often leave an athletic director with little choice but to replace a coach, especially in instances where winning is at a premium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dohrn et al (2015) found support for both the common sense and ritual scapegoating approaches within their study of National Collegiate Athletic Association (NCAA) football teams. Likewise, McTeer et al (1995) found that within-season coaching changes across four professional sports leagues in North America-the National Basketball Association (NBA), National Football League (NFL), National Hockey League (NHL), and MLB-were associated with improved post-change performance improvements during that season, but not in the subsequent season.…”
Section: Theory and Hypothesis Development Leader Transitionsmentioning
confidence: 99%
“…In terms of peer-reviewed literature that has examined the potential effects of coaching tenure on performance, there exists a subset of studies that have lent insights to this area. One such study was conducted by Dohrn, Lopez, and Reinhardt (2015) to look at leadership succession in NCAA football and the impact it had on FBS teams' financial and athletic performances over one, two, and four-season timeframes. Following a series of regression analyses, it was reported that new coaches positively and significantly impacted the on-field performances of teams over these time periods, as determined by absolute increases in Sagarin ratings, Sagarin ranks, and winning percentages.…”
Section: Literature Reviewmentioning
confidence: 99%